0018 Adverse childhood experiences, sexual orientation, and adult health: an analysis of north carolina, washington, and wisconsin behavioural risk factor surveillance system data. (26th April 2015) - Austin, Anna; Herrick, Harry; Proescholdbell, Scott
Abstract : Statement of purpose: Inclusion of questions regarding sexual orientation on population based surveys has helped begin to identify health disparities among individuals identifying as lesbian, gay, or bisexual (LGB). However, little research has explored the link between multiple forms of childhood adversity and a range of poor outcomes in adulthood among LGB individuals compared to heterosexuals. The purpose of this study was to utilise data from the North Carolina, Wisconsin, and Washington Behavioural Risk Factor Surveillance System (BRFSS) surveys to explore the association of sexual orientation with poor outcomes in adulthood before and after adjustment for exposure to adverse childhood experiences (ACEs). Methods/Approach: The study sample included all 2012 N.C., 2011 WA, and 2011 and 2012 WI BRFSS participants who responded to the ACE module and a question regarding sexual orientation. Descriptive statistics were used to define the prevalence of ACE categories by sexual orientation. Using sexual orientation as the primary independent variable, separate multivariate logistic regression models were conducted for perceived health, health risks, and chronic conditions outcomes. Results: Results revealed an increased prevalence of all ACE categories among LGB individuals compared to heterosexuals, particularly for sexual abuse, adult mental illness in the household, and an incarcerated household member. In multivariate analyses, after adjustment for demographics, sexual orientation was significantly associated with several outcomes. After additional adjustment for an ACE summary score, sexual orientation was no longer significantly associated with poor physical health, current smoking, and binge drinking while associations with poor mental health, activity limitation, HIV risk behaviours, current asthma, depression, and disability remained, but were attenuated. Conclusions: This study builds upon existing research by examining multiple forms of childhood adversity experienced by LGB individuals and the association of such experiences and sexual orientation with poor outcomes in adulthood. Significance and contribution to the field: Results provide additional insight into the potential effects of childhood adversity on previously identified health disparities among LGB individuals. As efforts continue in N.C. to incorporate assessment of ACEs and ACE prevention into primary care practice, these results reinforce the importance of culturally competent services that are sensitive to the unique needs and experiences of special populations.